Rethinking Sexuality in the Middle East and North Africa - (:unkn) unknown (The University of North Carolina Press, 2024)
In this volume, the chapters provide regional perspectives on some of the important institutions, movements, and issues related to sexuality(-ies) in the Middle East and North Africa (MENA) region, such as sexuality and the law, sexual rights movements, ...
Keywords: Sexualidad; Medio Oriente